(untitled) (American Journal of Islam and Society, 1991)
The present paper is a contribution to the building blocks of an investment model within the framework of an integrated macroeconomic model of an Islamic economy. Investment behavior in the model is guided by an Islamicethical value system and profit-sharing financial contracts. The typical firm’s investment decision is believed to emerge from a dynamic inter-temporal maximization exercise within an infinite time horizon. The method of Calculus of Variations is applied to arrive at the optimal investment and employment criteria for the firm. The result is then incorporated into a macroeconomic model to study the behavior of key endogenous variables like national income and the rate of profit-share. Comparative statics exercised within a general equilibrium framework reveal the potency of monetary policy but the neutrality of fiscal policy with respect to output and employment. Introduction The past decade has witnessed a tremendous outpouring of interest as well as effort in the formalization of economic models based on profit-sharing financial arrangements as an Islamic alternative to the conventional interestbased economic system. Several macroeconomic models for interest-free economies have been proposed (Anwar 1987; Habibi 1987; Metwally 1981 & 1983). The rigor of an integrated approach to such macroeconomic modelhg depends on the rigor of the component models, namely, the consumption, investment, monetary, and fiscal relationships. Economists have written extensively on different aspects of consumer behavior in Islamic societies. Kahf (1978) and Khan (1984), among others, have contributed to the conceptual and analytical formulation of the consumption function under ...